Singlet Fission in a New Series of Systematically Designed Through‐space Coupled Tetracene Oligomers - Majdecki, Maciej; Hsu, Chao‐Hsien; Wang, Chih‐Hsing; Shi, Emily Hsue‐Chi; Zakrocka, Magdalena; Wei, Yu‐Chen; Chen, Bo‐Han; Lu, Chih‐Hsuan; Yang, Shang‐Da; Chou, Pi‐Tai; Gaweł, Przemysław (Angewandte Chemie International Edition, 2024)
Singlet fission (SF) holds great promise for current photovoltaic technologies, where tetracenes, with their relatively high triplet energies, play a major role for application in silicon‐based solar cells. However, the SF efficiencies in tetracene dimers are low due to the unfavorable energetics of their singlet and triplet energy levels. In the solid state, tetracene exhibits high yields of triplet formation through SF, raising great interest about the underlying mechanisms. To address this discrepancy, we designed and prepared a novel molecular system based on a hexaphenylbenzene core decorated with 2 to 6 tetracene chromophores. The spatial arrangement of tetracene units, induced by steric hindrance in the central part, dictates through‐space coupling, making it a relevant model for solid‐state chromophore organization. We then revealed a remarkable increase in SF quantum yield with the number of tetracenes, reaching quantitative (196 %) triplet pair formation in hexamer. We observed a short‐lived correlated triplet pair and limited magnetic effects, indicating ineffective triplet dissociation in these through‐space coupled systems. These findings emphasize the crucial role of the number of chromophores involved and the interchromophore arrangement for the SF efficiency. The insights gained from this study will aid designing more efficient and technology‐compatible SF systems for applications in photovoltaics. A collection of through‐space tetracene oligomers demonstrates sub‐picosecond singlet fission, as revealed by femtosecond‐resolved transient absorption spectroscopy. These oligomers exhibit a remarkably high yield of the triplet pair state, a characteristic seldom observed in tetracene derivatives owing to the unfavorable energetics associated with their singlet and triplet energy levels.